О РАЗНООБРАЗИИ ГИДРОФАУНЫ ПРАВЫХ ПРИТОКОВ РЕКИ ИЛЕ В ПРЕДЕЛАХ РЕСПУБЛИКИ КАЗАХСТАН (ҚазҰУ хабаршысы. Экология сериясы, 2016)
By the period 2007-2011 the macrozoobenthos and fishpopulation were investigated at the right tributaries of the River Ili in the Republic of Kazakhstan. 21 species offish and 78 bottom and benthic invertebrates are identified. An analysis of the current species composition offloodplain waterbodies and watercourses lowlandand mountain areas, in comparison with previously published data are described in the artical.